Manufacturing method for active material layer for battery, active material layer for battery, and battery
The method of manufacturing a battery active material layer using femtosecond laser irradiation addresses the challenge of reducing battery resistance while maintaining capacity by sublimating the binder and enhancing electrolyte penetration without active material loss.
Patent Information
- Application Number
- JP2023146451
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-09-08
AI Technical Summary
Existing battery manufacturing methods using nonaqueous electrolytes face challenges in reducing battery resistance while maintaining battery capacity, as conventional methods can lead to a reduction in active material and impaired electrolyte permeability.
A method for manufacturing a battery active material layer involves preparing a layer with a binder and active material, and then locally irradiating it with a femtosecond laser under specific conditions to sublimate the binder, reducing particle size and enhancing electrolyte penetration without removing active material.
This approach effectively reduces battery resistance by improving electrolyte permeability while preventing a reduction in battery capacity by minimizing active material loss during the laser irradiation process.
Smart Images

Figure 2025039385000002 
Figure 2025039385000003 
Figure 2025039385000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for producing an active material layer for a battery, an active material layer for a battery, and a battery. [Background technology]
[0002] 2. Description of the Related Art Conventionally, in liquid batteries using an electrolyte solution, an active material layer containing a binder and an active material has been used.
[0003] For example, Patent Document 1 discloses a nonaqueous electrolyte battery comprising an electrode group, an exterior material, and a nonaqueous electrolyte, the electrode group comprising a positive electrode, a negative electrode, and a separator, the positive electrode having a positive electrode current collector, and a positive electrode layer containing a positive electrode active material and a binder and formed on the positive electrode current collector, the negative electrode having a negative electrode current collector, and a negative electrode layer containing a negative electrode active material and a binder and formed on the negative electrode current collector, the separator being interposed between the positive electrode layer and the negative electrode layer and wound together with the positive electrode and the negative electrode, at least one of the positive electrode layer and the negative electrode layer being formed on its surface side so as to connect both long sides (S), having less binder than the surface side of the other region (R), and having a plurality of permeation promoting portions that promote permeation of the nonaqueous electrolyte from the surface side of the region (R). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2011-171020 A Summary of the Invention [Problem to be solved by the invention]
[0005] Patent Document 1 discloses a method for forming an area with less binder on the surface of an electrode layer of a battery using a non-aqueous electrolyte by using a CW laser. However, the active material is removed from the electrode layer by the laser irradiation, and the amount of the active material is reduced, which results in a decrease in the battery capacity.
[0006] In addition, the permeability of an electrolyte into an active material layer of a battery affects the resistance of the battery, and therefore it is desirable to reduce the resistance of the battery by improving the permeability of the electrolyte into the active material layer.
[0007] The present disclosure has been made in consideration of the above circumstances, and aims to provide a method for manufacturing an active material layer for a battery, which can reduce the resistance of a battery while suppressing a reduction in battery capacity, an active material layer for a battery, and a battery having the active material layer for a battery. [Means for solving the problem]
[0008] Means for solving the above problems include the following aspects. <1> providing an active material layer including a binder and an active material; A femtosecond laser was applied to the active material layer with a heat dose of 0.04 J / mm 2 More than 0.32J / mm 2 and an irradiation step of irradiating under the following conditions: <2> The irradiation step is a step of irradiating a femtosecond laser under the conditions of an output of 10 W or more and 150 W or less and an overlap rate of 0% or more and 37.5% or less. <1> 2. A method for producing the active material layer for a battery according to claim 1 . <3> An active material layer for a battery comprising a binder and an active material, A battery active material layer, wherein the brightness of a surface image obtained by EPMA mapping after dyeing the binder is lower than the brightness of a cross-section image at a depth of 20 μm obtained by EPMA mapping. <4> An active material layer for a battery comprising a binder and an active material, An active material layer for a battery, wherein the binder has an average particle size of 10.0 μm or less in a surface image obtained by EPMA mapping after dyeing the binder. <5> <3> or <4> 2. A battery comprising the active material layer for a battery according to claim 1 as at least one of a positive electrode active material layer and a negative electrode active material layer. Effect of the Invention
[0009] According to the present disclosure, there are provided a method for manufacturing an active material layer for a battery, which can reduce the resistance of a battery while suppressing a reduction in battery capacity, an active material layer for a battery, and a battery having the active material layer for a battery. [Brief description of the drawings]
[0010] [Figure 1] 1 is a graph showing the results of measuring the change in mass (mass loss (%)) of an active material layer before and after femtosecond laser irradiation in Examples and Comparative Examples. [Diagram 2] 1 is a graph showing the results of measuring battery resistance in Examples and Reference Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment that is an example of the present disclosure will be described. These descriptions and examples are merely illustrative of the embodiment, and are not intended to limit the scope of the invention. In the present specification, the upper or lower limit of one numerical range may be replaced with the upper or lower limit of another numerical range. In addition, in the present specification, the upper or lower limit of the numerical range may be replaced with a value shown in the examples.
[0012] Each component may contain multiple types of the corresponding substance. When referring to the amount of each component in a composition, if the composition contains multiple substances corresponding to each component, the amount refers to the total amount of those multiple substances present in the composition, unless otherwise specified. The term "process" includes not only independent processes, but also processes that cannot be clearly distinguished from other processes as long as the intended effect of the process is achieved.
[0013] <Method of manufacturing active material layer for battery> A method for producing an active material layer for a battery according to an embodiment of the present disclosure includes a step of preparing an active material layer including a binder and an active material, and applying a femtosecond laser to the active material layer with a heat amount of 0.04 J / mm 2 More than 0.32J / mm 2 and an irradiation step of irradiating under the following conditions.
[0014] In the method for producing an active material layer for a battery according to an embodiment of the present disclosure, a femtosecond laser is locally irradiated onto the surface of the active material layer, and the laser irradiation is performed at a rate of 0.04 J / mm 2 The above heat input is applied. Therefore, the binder on the surface of the active material layer is sublimated, and the particle size of the binder can be reduced. This ensures a reaction surface on the surface of the active material layer, and a permeation path for the electrolyte into the active material layer is ensured, and as a result, the resistance of the battery including this active material layer can be reduced.
[0015] In addition, a femtosecond laser is used as the laser to irradiate the surface of the active material layer, and the input heat amount during the femtosecond laser irradiation is 0.32 J / mm 2 In other words, the surface of the active material layer is locally irradiated with a femtosecond laser while the total amount of heat is suppressed. This suppresses the removal of the active material from the active material layer by the laser irradiation, suppresses the mass loss of the active material, and suppresses the reduction in the battery capacity of a battery including this active material layer.
[0016] Hereinafter, each step of the method for producing an active material layer for a battery according to an embodiment of the present disclosure will be described.
[0017] -Step of preparing active material layer- A method for producing an active material layer for a battery according to an embodiment of the present disclosure includes a step of preparing an active material layer including a binder and an active material. The active material layer may be either a negative electrode active material layer or a positive electrode active material layer. The negative electrode active material layer and the positive electrode active material layer may be formed by a conventional method. For example, the active material layer may be formed by applying a solution containing raw materials for the active material layer and drying it.
[0018] Hereinafter, the active materials, binders, etc. will be described separately for the negative electrode active material layer and the positive electrode active material layer.
[0019] ·Negative electrode active material layer Examples of the negative electrode active material include graphite-based carbons such as natural graphite, artificial graphite, and amorphous-coated graphite. The proportion of graphite in the graphite-based carbon is generally 50% by mass or more, preferably 80% by mass or more. Examples of the binder contained in the negative electrode active material include rubbers such as styrene-butadiene copolymer (SBR), and vinyl halide resins such as polyvinylidene fluoride (PVdF). The negative electrode active material layer may further contain other components such as a thickener. Examples of the thickener include celluloses such as carboxymethyl cellulose (CMC).
[0020] ·Positive electrode active material layer Examples of the positive electrode active material include lithium nickel cobalt manganese composite oxide (hereinafter sometimes simply referred to as "LNCM"). The simplest LNCM has the following general formula: LiNi x Co y Mn z O 2 (where x, y, z satisfy 0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z = 1). LNCM may contain other additive elements in addition to Li, Ni, Co, and Mn, such as transition metal elements other than Ni, Co, and Mn, and typical metal elements other than Li. LNCM has a layered crystal structure. LNCM should exceed 50% by mass of the entire positive electrode active material, for example, occupy 80 to 100% by mass. The positive electrode active material may be composed of only LNCM. Examples of other positive electrode active materials include lithium nickel composite oxide, lithium cobalt composite oxide, lithium nickel manganese composite oxide, etc.
[0021] Examples of the binder contained in the positive electrode active material layer include vinyl halide resins such as polyvinylidene fluoride (PVdF). The positive electrode active material layer may further contain other components, such as a conductive material, etc. Examples of the conductive material include non-graphitizable carbon, easily graphitizable carbon such as carbon black, and graphite.
[0022] -Irradiation process- Next, in the irradiation process, a femtosecond laser is applied to the active material layer with a heat dose of 0.04 J / mm 2 More than 0.32J / mm 2 Irradiate under the following conditions: The femtosecond laser means a pulse laser with a pulse width of 1 fs or more and 500 fs or less. The pulse width of the femtosecond laser is preferably 1 fs or more and 100 fs or less.
[0023] ·Input heat amount The amount of heat emitted by the femtosecond laser to the active material layer in the irradiation process is 0.04 J / mm 2 More than 0.32J / mm 2 The following applies. Input heat amount is 0.04J / mm 2 By setting the heat input amount to 0.32 J / mm or more, the binder on the surface of the active material layer can be sublimated to reduce the particle size of the binder. Therefore, a permeation path of the electrolyte into the active material layer can be secured, thereby reducing the resistance in the battery including the active material layer. 2 By making the thickness of the active material layer or less, removal of the active material from the active material layer due to laser irradiation is suppressed, and a reduction in the battery capacity of a battery including the active material layer is suppressed. The lower limit of the input heat is 0.07 J / mm 2 It is preferable that the value is 0.10 J / mm or more. 2 On the other hand, the upper limit of the input heat amount is preferably 0.25 J / mm 2 It is preferable that the value is less than 0.20 J / mm 2 It is more preferable that:
[0024] The amount of heat input from the femtosecond laser can be controlled, for example, by adjusting the power and the wrap rate.
[0025] ·output From the viewpoint of reducing the resistance of the battery while suppressing a reduction in the battery capacity, the output of the femtosecond laser is preferably 10 W or more and 150 W or less, more preferably 20 W or more and 150 W or less, and even more preferably 30 W or more and 100 W or less.
[0026] Wrap Rate From the viewpoint of reducing the resistance of the battery while suppressing a reduction in the battery capacity, the overlap rate when irradiating the femtosecond laser is preferably 0% or more and 37.5% or less, more preferably 0% or more and 30% or less, and even more preferably 0% or more and 15% or less.
[0027] Here, the overlap rate means the ratio of the area of the region irradiated with the femtosecond laser in an overlapping manner, and is expressed by the following formula. Formula: (area where lasers are overlapping and irradiated) / (area where lasers are overlapping and irradiated)+(area where lasers are not overlapping and irradiated) A femtosecond laser is a pulsed laser with a pulse width as short as a femtosecond level, and irradiation is repeated for a short time while moving the laser irradiation position slightly, thereby irradiating the entire area to be irradiated. The area irradiated with overlapping lasers refers to an area irradiated with a laser that overlaps with the previous irradiation area because the movement of the irradiation position is small during repeated laser irradiation while moving the irradiation position. For example, when repeated irradiation is performed without moving the irradiation position at all, the overlap rate is 100%, and when repeated irradiation is performed by moving the irradiation position so as to deviate from the area irradiated by one laser irradiation, the overlap rate is 0%. The overlap rate can be controlled, for example, by adjusting the moving distance during repeated laser irradiation.
[0028] Frequency, pulse energy When irradiating with a femtosecond laser, it is preferable to further adjust the frequency, pulse energy, and the like. The frequency at which the femtosecond laser is irradiated is preferably 100 kHz or more and 3 MHz or less, more preferably 300 kHz or more and 2.5 MHz or less, and even more preferably 500 kHz or more and 2 MHz or less, from the viewpoint of reducing the resistance of the battery while suppressing a reduction in the battery capacity in the battery. From the viewpoint of reducing the resistance of the battery while suppressing a reduction in the battery capacity, the pulse energy when irradiating the femtosecond laser is preferably 0.01 mJ or more and 0.4 mJ or less, more preferably 0.03 mJ or more and 0.3 mJ or less, and even more preferably 0.05 mJ or more and 0.2 mJ or less.
[0029] <Battery active material layer> -First active material layer- In the present disclosure, an active material layer for a battery according to a first embodiment (simply referred to as a "first active material layer") contains a binder and an active material, and the brightness of a surface image obtained by EPMA mapping after dyeing the binder is lower than the brightness of a cross-section image at a depth of 20 μm obtained by EPMA mapping.
[0030] The fact that the luminance at the surface of the active material layer is lower than the luminance at a cross section 20 μm deep from the surface indicates that the particle size of the binder at the surface of the active material layer is smaller, which ensures a reaction surface at the surface of the active material layer and a permeation path for the electrolyte into the active material layer, thereby reducing the resistance in a battery including this active material layer.
[0031] The first active material layer can be obtained, for example, by the method for producing an active material layer for a battery according to the embodiment of the present disclosure described above.
[0032] -Second active material layer- In the present disclosure, an active material layer for a battery according to a second embodiment (simply referred to as a "second active material layer") contains a binder and an active material, and the average particle size of the binder in a surface image obtained by EPMA mapping after dyeing the binder is 10.0 μm or less.
[0033] Since the average particle size of the binder on the surface of the active material layer is small, being 10.0 μm or less, a reaction surface is secured on the surface of the active material layer, and a penetration path for the electrolyte into the active material layer is secured, thereby reducing the resistance in a battery including this active material layer.
[0034] In the second active material layer, the average particle size of the binder on the surface is 10.0 μm or less, preferably 7.0 μm or less, and more preferably 6.0 μm or less. The lower limit of the average particle size of the binder is, for example, preferably 2.0 μm or more, and more preferably 4.0 μm or more.
[0035] The second active material layer can be obtained, for example, by the method for producing an active material layer for a battery according to the embodiment of the present disclosure described above.
[0036] Here, a method for measuring the luminance on the surface of the active material layer and the average particle size of the binder will be described. First, the active material layer is dyed (e.g., osmium (Os) dyed) according to the binder contained therein. Next, an EPMA (Electron Probe Micro Analysis) mapping image is obtained for the surface of the dyed active material layer. The brightness is measured from the obtained mapping image. Furthermore, the top 10% of brightness data is calculated, and this brightness data is set as a threshold value to perform binarization processing. From the binarized image, the particle diameter of the binder particles (meaning the length of the longest part in the image of the target binder particle) is measured. This measurement is performed for 20 binder particles, and the arithmetic average value is taken as the average particle diameter. The luminance of the binder at a cross section 20 μm deep from the surface is measured by exposing the cross section 20 μm deep from the surface by a method such as cutting, and then measuring the luminance at the surface of the active material layer in the same manner as described above.
[0037] <Battery> The battery according to the embodiment of the present disclosure has the above-mentioned first active material layer or second active material layer as at least one of the positive electrode active material layer and the negative electrode active material layer. The battery includes, for example, a negative electrode, a positive electrode, a separator, and an electrolyte.
[0038] (electrolyte) ·solvent The electrolytic solution contains a solvent (non-aqueous solvent) and an electrolyte. Examples of the solvent (non-aqueous solvent) include N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(fluorosulfonyl)imide (DEME), 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide (EMI), and 1-ethyl-2,3-dimethylimidazolium bis(fluorosulfonyl)imide (DEMI-FSI).
[0039] ·Electrolyte The electrolyte in the electrolytic solution may be, for example, a Li salt. Examples of the Li salt include lithium bis(fluorosulfonyl)imide (LiFSI), LiPF 6 (lithium hexafluorophosphate), lithium tetrafluoroborate (LiBF 4 ), Li[N(CF 3 SO 2 ) 2 ] etc. The amount of the electrolyte may be, for example, 1.0 to 2.0 mol / L, and is preferably 1.0 to 1.5 mol / L.
[0040] The electrolytic solution may contain various additives, such as a thickener, a film-forming agent, a gas generating agent, etc., in addition to the solvent and the electrolyte. The electrolyte is typically a non-aqueous electrolytic solution that is liquid at room temperature (e.g., 25±10°C). The electrolytic solution is typically liquid in the environment in which the battery is used (e.g., a temperature environment of -20 to +60°C).
[0041] (Negative electrode) The negative electrode includes, for example, a negative electrode current collector and a negative electrode active material layer fixed on the negative electrode current collector. The negative electrode current collector is preferably a conductive member made of a metal having good electrical conductivity (e.g., copper). The negative electrode active material layer may be, for example, the first active material layer or the second active material layer described above.
[0042] (positive electrode) The positive electrode includes, for example, a positive electrode current collector and a positive electrode active material layer fixed on the positive electrode current collector. The positive electrode current collector is preferably a conductive member made of a metal having good electrical conductivity (e.g., aluminum). The positive electrode active material layer may be, for example, the first active material layer or the second active material layer described above.
[0043] (Separator) The separator is an electrically insulating porous film. The separator electrically isolates the positive electrode and the negative electrode. The separator may have a thickness of, for example, 5 to 30 μm. The separator may be composed of, for example, a porous polyethylene (PE) film, a porous polypropylene (PP) film, or the like. The separator may have a multi-layer structure. For example, the separator may be composed of a porous PP film, a porous PE film, and a porous PP film laminated in this order. The separator may have a heat-resistant layer on its surface. The heat-resistant layer includes a heat-resistant material. Examples of the heat-resistant material include metal oxide particles such as alumina, and high-melting point resins such as polyimide.
[0044] (Application) Applications of the battery include, for example, power sources for hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), battery electric vehicles (BEVs), and the like. EXAMPLES
[0045] Hereinafter, the present disclosure will be described based on examples, but the present disclosure is not limited to these examples. In the following description, unless otherwise specified, all "parts" and "%" are based on mass.
[0046] <Examples 1 to 3, Comparative Example 1> In each of the examples and comparative examples, the femtosecond laser output and overlap rate of the irradiated active material layer having the composition shown below were adjusted as shown in Table 1 to change the amount of heat input, and the laser was irradiated onto the surface of the active material layer. (Irradiation conditions) Laser pulse width: 500fs (0.0005ns), power: 100W, frequency: 500kHz-2MHz, pulse energy: 0.05mJ-0.2mJ, overlap rate: 0%-62.5% Composition of active material layer: negative electrode active material = graphite, binder = styrene butadiene copolymer (SBR), thickener = carboxymethyl cellulose (CMC), conductive material: carbon nanotubes (CNT)
[0047] [Table 1]
[0048] <Evaluation> (1) Mass loss In each of the Examples and Comparative Examples, the change in mass (mass loss (%)) of the active material layer was measured before and after the femtosecond laser irradiation, and the results are shown in a graph in FIG.
[0049] As shown in the graph in FIG. 1, in Example 1 (input heat amount 0.04 J / mm 2 ), Example 2 (0.11 J / mm 2 ), and Example 3 (0.32 J / mm 2 ), the mass loss of the active material layer was suppressed to 6% or less, whereas in Comparative Example 1 (input heat amount 0.53 J / mm 2 ) the mass loss of the active material layer exceeded 6%.
[0050] (2) Battery resistance Batteries were fabricated using the active material layers of Examples 1 and 2, which had little mass loss, and a battery resistance test was performed. In addition, as a reference example (Reference: Ref), a battery resistance test was also performed on an active material layer whose surface was not irradiated with a femtosecond laser. The evaluation results are shown in a graph in Figure 2, which plots the ratio (%) of the reference example (Ref). The battery configuration in the battery resistance test was a lamicelle type (positive electrode 45 mm x 47 mm, negative electrode 47 mm x 49 mm).
[0051] As shown in the graph of FIG. 2, it is understood that in Examples 1 and 2, the battery resistance can be reduced compared to the reference example (Ref).
[0052] (3) Average particle size of binder For Example 1 and the above-mentioned Reference Example (Reference: Ref), the average particle size of the binder was measured in a surface image obtained by EPMA mapping after dyeing the binder. The active material layers of Example 1 and Reference Example were stained with osmium (Os), and EPMA (Electron Probe Micro Analysis) mapping images were obtained for the stained active material layer surfaces. The top 10% brightness data was calculated from the mapping images, and binarization processing was performed by setting this brightness data as a threshold value. From the binarized images, the particle diameter (longest length) of the binder (SBR) particles was measured for 20 binder particles, and the arithmetic average value was taken as the average particle diameter. The results are shown below. -Average particle size- Example 1: 7.7 μm Reference example (Ref): 17μm
Claims
1. providing an active material layer including a binder and an active material; A femtosecond laser was applied to the active material layer with a heat amount of 0.04 J / mm 2 0.32J / mm or more 2 and an irradiation step of irradiating under the following conditions:
2. 2 . The method for producing an active material layer for a battery according to claim 1 , wherein the irradiation step is a step of irradiating with a femtosecond laser under conditions of an output of 10 W or more and 150 W or less and an overlap ratio of 0% or more and 37.5% or less.
3. An active material layer for a battery comprising a binder and an active material, A battery active material layer, wherein the brightness of a surface image obtained by EPMA mapping after dyeing the binder is lower than the brightness of a cross-section image at a depth of 20 μm obtained by EPMA mapping.
4. An active material layer for a battery comprising a binder and an active material, An active material layer for a battery, wherein the binder has an average particle size of 10.0 μm or less in a surface image obtained by EPMA mapping after dyeing the binder.
5. A battery comprising the active material layer for a battery according to claim 3 or 4 as at least one of a positive electrode active material layer and a negative electrode active material layer.
Citation Information
Patent Citations
Manufacture of nonaqueous electrolyte secondary battery electrode and nonaqueous electrolyte secondary battery using it
JP2001035482A
Electrode for lithium secondary battery, and lithium secondary cell
JP2010086717A
Nonaqueous electrolyte battery
JP2011171020A
Method for manufacturing electrode for lithium secondary battery, electrode for lithium secondary battery, and lithium secondary battery
JP2013097925A
KR20210081155A